Turasth–Based Model for Islamic Education Policy Analysis: A Case Study of Madrasah Tsanawiyah - Dian Rusydianti; Eko Sumadi; Masrukhin Masrukhin (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study explores a turath-based model for Islamic education policy analysis through a case study at MTs Mazroatul Huda Karanganyar, Demak. The study is motivated by the growing concern over moral degradation among students in the digital era and the urgent need to strengthen value-based Islamic education. Although classical Islamic texts (turath) have historically played a central role in shaping students' moral and spiritual character, their integration into contemporary educational policy and learning practices remains underexplored. Therefore, this research aims to analyze the instructional strategies used in teaching turath texts, identify the challenges encountered in the learning process, and formulate practical solutions for strengthening the internalization of aqidah and akhlak values among students. This research employs a descriptive qualitative method with a case study approach. Data were collected through classroom observations, in-depth interviews with teachers and school leaders, and supporting documentation. The findings indicate that the integration of traditional learning methods, particularly sorogan and bandongan, with modern pedagogical approaches can effectively support the internalization of Islamic values among students. However, several challenges were identified, including limited Arabic language proficiency, students' learning motivation, and restricted instructional time. To address these issues, the institution implemented several strategies, including teacher professional development, interactive learning methods, and stronger collaboration with parents. This study highlights the importance of a holistic learning model supported by continuous evaluation in developing Islamic education that is both relevant and responsive to contemporary challenges. The findings contribute to the development of a conceptual framework for integrating turath-based learning into Islamic education policy and practice.